The EmPanados: the poetics of creating characters in fabric - Goulart, Fábio Ortiz; Maio, José Endrew Vieira (Revista do Colóquio, 2023)
Fabric is one of the materials with the greatest presence in our daily lives, after all, without it, our bodies would be uncovered and when we sleep we use fabrics to cover ourselves from the cold. Relegated to the status of material for the production of "minor art", fabrics were forgotten, being rarely used as material for production in the field of visual poetics. A very versatile material, the fabric allows us to create very broad shapes. In contemporary art, the possibilities of this material have started to be widely explored. In this work, based on references such as Clau Paranhos with his "Ugly Dolls" and Celi Ortiz with her production of sponge cats, I seek to explore the possibilities of recycled fabric for creating characters, which dialogue with the universe of childhood and donate toys , from the EmPanados series.